Pengaruh Digital Payment Terhadap Pertumbuhan Ekonomi Indonesia: Analisis Kawasan di Indonesia Selama Pandemi Covid-19 - Maharani, Dian Putri; Romiza, Naziha; Pasaribu, Esti; Febriani, Ratu Eva (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2023)
A country's payment system plays an important role in the country's economic development. In recent years, economic transactions have been carried out digitally or without cash worldwide, including in Indonesia. Digitalizing the payment system means switching from a paper-based payment system to a digital/electronic one. Digital payments offer speed, lower fees, and convenience. A well-functioning digital payments system is critical to a country's overall economic performance, monetary policy, and financial stability. This study aims to determine the effect of digital payments on economic growth in Indonesia during the COVID-19 pandemic. Digital payment measured by regional ATM and ATM+Debit transaction volume. Economic growth is measured from GRDP-ADHK. To achieve this, the study employed regional analysis. The data were manifested in the form of panel data and gathered from 34 provinces in Indonesia. The data covered those between 2019 to 2021. Having collected the data, they were analyzed using the multiple regression analysis. In particular, it employed a specific method, what is known as the Eviews 12 program. The results of this research were mixed. For example, of many provinces in Indonesia, digital payments had the greatest influence on the provinces of Sumatra Island. It has a significant positive effect on the province’s economic growth. In other islands, like Java-Bali, digital payments were reported to have no significant positive effect on economic growth. Meanwhile, on the eastern Indonesian islands, digital payments were recorded to have absolutely no effect on economic growth.